English Language Teaching in Zambia: Balancing Colonial Legacies and Cultural Relevance (British Journal of Multidisciplinary and Advanced Studies, 2025)
The teaching of English in Zambia plays a crucial role in the education system, serving as the dominant medium of instruction at all academic levels. However, the multilingual nature of the country presents significant challenges, as many students learn English as a second or third language. This study investigates the effectiveness and cultural relevance of English Language Teaching (ELT) methods employed in Zambian secondary schools. Using a qualitative research design, the study explores how teachers adapt their instructional strategies to Zambia’s diverse linguistic and cultural context. Data were collected through semi-structured interviews with English teachers from various schools and analyzed using thematic analysis within a postcolonial theoretical framework. Findings indicate that teachers employ a combination of traditional and modern ELT methods, including Communicative Language Teaching (CLT), Grammar-Translation, Task-Based Learning (TBL), and teacher exposition. While communicative approaches have gained traction, the persistence of grammar-translation and lecture-based instruction reflects the lasting influence of Zambia’s colonial educational heritage. Teachers have made efforts to integrate culturally relevant pedagogy by incorporating local proverbs, storytelling, and translanguaging strategies to enhance student engagement. However, challenges such as large class sizes, limited teaching resources, and examination-driven curricula hinder the full implementation of culturally responsive teaching methods. The study highlights the ongoing tension between the need for English proficiency in a globalized world and the importance of preserving local linguistic and cultural identities. It recommends policy reforms that support more inclusive and culturally adaptable ELT strategies to bridge the gap between colonial legacies and contemporary multilingual realities in Zambia’s education system.